Efficient quantum secret sharing based on polarization and orbital angular momentum. (17th February 2019) - Qin, Huawang; Tso, Raylin
ABSTRACT: An efficient quantum secret sharing scheme is proposed. In the proposed scheme, the polarization state and the orbital angular momentum state of the particle can be utilized simultaneously. One state is used to bring the secret information, and the other state is used to check the eavesdropping. So all the particles can be used to transmit the secret, and the utilization efficiency of particles can achieve 100%. Compared to the existing schemes based on BB84 protocol or decoy particles, our scheme can increase the utilization efficiency of particles effectively.